Ado????o de pr??ticas de TI verde em procedimentos da pol??cia militar do estado de S??o Paulo - Penha, Marcelo (2017)
This dissertation aims to report on the implementation of the concept of Green IT in the Mail and Archive Sector of the Administrative Support Department of the General Command (DSACG) of the Military Police of the State of S??o Paulo (PMESP), in order to reduce the impacts Environmental and economic impacts caused by the use of printing supplies. For that, a qualitative research was developed, with multiple sources of evidence, such as: direct and participant observation, documentary analysis and interviews. This research may also be classified as exploratory, as it has developed a detailed analysis of the existing situations in the DSACG Mail and Archive Sector. The research-action methodology was used for this work, because the researcher and the collaborators of the organization are involved and interact, in a cooperative and participatory way in the resolution of the problem under study. In order to fulfill the objectives of this research, a previous diagnosis was made by the Sector under study that identified its functioning and routines. Next, Green IT actions were applied based on the concept of Green IT, in order to reduce the costs of the Sector and study with inputs and consequent environmental impacts. The determined actions were communicated to the employees through training. After implementation, these actions were evaluated, improved and monitored. We also conducted a semi-structured interview through questionnaires with managers of large companies that implemented Green IT actions in order to reduce printing expenses in order to evaluate their procedures and compare them with those applied by this research. This work has shown that it is possible to reduce spending on print supplies and minimize the waste generated by using the printer only by employing Green IT actions in the Mail and Archive Sector And making employees of the organization aware, the results were positive, but as a suggestion for new research, the question is: could it be possible to maximize the positive actions of the Green IT practice and increase them as a practice for all police in Brazil?